1993
DOI: 10.1128/aem.59.10.3250-3254.1993
|View full text |Cite
|
Sign up to set email alerts
|

Effect of monensin on the specific activity of ammonia production by ruminal bacteria and disappearance of amino nitrogen from the rumen

Abstract: When unadapted mixed ruminal bacteria (312 mg of protein per liter) were treated with monensin (5 mM) in vitro, the rates of ammonia production from enzymatic digests of casein, gelatin, and soy protein (0.5 g of N per liter) were decreased from 46 2 to 24 1, 20 1 to 7 1, and 40 + 2 to 18 2 nmol/mg of protein per min, respectively. Monensin also caused a decrease in ammonia production in vivo. Nonlactating dairy cows which were fed 0.56 kg of timothy hay 12 times per day had a steady-state ruminal ammonia conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 36 publications
1
34
0
2
Order By: Relevance
“…Earlier studies suggested that monensin causes a decreased degradation of CP in the rumen through an inhibitory effect on HAP bacteria (Wischer et al, 2013). A decrease in rumen liquid NH 3 -N concentrations and HAP bacteria have been described under the influence of monensin in vitro (Yang and Russell, 1993a;Eschenlauer et al, 2002) as well as in vivo (Yang and Russell, 1993b;Ruiz et al, 2001). In the current study, we did not observe lower NH 3 -N concentrations in the rumen of the monensin-supplemented animals and, to our knowledge, none of the bacteria that were decreased under the influence of monensin have been described as high amino acid fermenters.…”
Section: Effect Of Monensin On Rumen Microbiotamentioning
confidence: 99%
“…Earlier studies suggested that monensin causes a decreased degradation of CP in the rumen through an inhibitory effect on HAP bacteria (Wischer et al, 2013). A decrease in rumen liquid NH 3 -N concentrations and HAP bacteria have been described under the influence of monensin in vitro (Yang and Russell, 1993a;Eschenlauer et al, 2002) as well as in vivo (Yang and Russell, 1993b;Ruiz et al, 2001). In the current study, we did not observe lower NH 3 -N concentrations in the rumen of the monensin-supplemented animals and, to our knowledge, none of the bacteria that were decreased under the influence of monensin have been described as high amino acid fermenters.…”
Section: Effect Of Monensin On Rumen Microbiotamentioning
confidence: 99%
“…Most obligate amino acid-fermenting bacteria are closely related to clostridia, but Attwood et al [37] isolated one strain that was more closely related to Fusobacterium necrophorum. When cattle were fed timothy hay, monensin caused a 40% decrease in ruminal ammonia, and this decrease could be explained by an inhibition of deamination [38]. Cattle not fed monensin had a speci¢c deamination rate of 27 nmol ammonia mg protein 31 min 31 .…”
Section: E¡ect Of Ionophores On Ruminal Bacteriamentioning
confidence: 99%
“…Ruminal fluid ammonia-N concentration (Table 1) was lower (P<0.05) for goats infused hainanmycin than infused the solution of ethanol and water. Decreased ruminal ammonia N concentrations (Dinius et al, 1976;Yang and Russell, 1993) could denote suppressed microbial degradation of protein and/or amino acids. This may be due to the ionophore inhibiting the growth of proteolytic ruminal bacteria (Nowbold et al, 1988;Lana and Russell, 1997).…”
Section: Volatile Fatty Acid Ammonia-n and Microbial Protein-n In Rumentioning
confidence: 99%